Oral Dipeptidyl Peptidase-4 Inhibitor Sitagliptin Increases Circulating Endothelial Progenitor Cells in Patients With Type 2 Diabetes: Possible role of stromal-derived factor-1α - Fadini, Gian Paolo; Boscaro, Elisa; Albiero, Mattia; Menegazzo, Lisa; Frison, Vera; de Kreutzenberg, Saula; Agostini, Carlo; Tiengo, Antonio; Avogaro, Angelo (Diabetes care, 2010)
OBJECTIVE: Vasculoprotective endothelial progenitor cells (EPCs) are regulated by stromal-derived factor-1α (SDF-1α) and are reduced in type 2 diabetes. Because SDF-1α is a substrate of dipeptidyl-peptidase-4 (DPP-4), we investigated whether the DPP-4 inhibitor sitagliptin modulates EPC levels in type 2 diabetic patients. RESEARCH DESIGN AND METHODS: This was a controlled, nonrandomized clinical trial comparing 4-week sitagliptin (n = 16) versus no additional treatment (n = 16) in addition to metformin and/or secretagogues in type 2 diabetic patients. We determined circulating EPC levels and plasma concentrations of SDF-1α, monocyte chemoattractant protein-1 (MCP-1), vascular endothelial growth factor (VEGF), and nitrites/nitrates. RESULTS: There was no difference in clinical baseline data between the sitagliptin and control arms. After 4 weeks, as compared with control subjects, patients receiving sitagliptin showed a significant increase in EPCs and SDF-1α and a decrease in MCP-1. CONCLUSIONS: Sitagliptin increases circulating EPCs in type 2 diabetic patients with concomitant upregulation of SDF-1α. This ancillary effect of DPP-4 inhibition might have potential favorable cardiovascular implications.